The Agropyron cristatum karyotype, chromosome structure and cross-genome homoeology as revealed by fluorescence in situ hybridization with tandem repeats and wheat single-gene probes - Said, Mahmoud; Hřibová, Eva; Danilova, Tatiana V; Karafiátová, Miroslava; Čížková, Jana; Friebe, Bernd; Doležel, Jaroslav; Gill, Bikram S; Vrána, Jan (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2018)
Fluorescence in situ hybridization with probes for 45 cDNAs and five tandem repeats revealed homoeologous relationships of Agropyron cristatum with wheat. The results will contribute to alien gene introgression in wheat improvement. Crested wheatgrass (Agropyron cristatum L. Gaertn.) is a wild relative of wheat and a promising source of novel genes for wheat improvement. To date, identification of A. cristatum chromosomes has not been possible, and its molecular karyotype has not been available. Furthermore, homoeologous relationship between the genomes of A. cristatum and wheat has not been determined. To develop chromosome-specific landmarks, A. cristatum genomic DNA was sequenced, and new tandem repeats were discovered. Their distribution on mitotic chromosomes was studied by fluorescence in situ hybridization (FISH), which revealed specific patterns for five repeats in addition to 5S and 45S ribosomal DNA and rye subtelomeric repeats pSc119.2 and pSc200. FISH with one tandem repeat together with 45S rDNA enabled identification of all A. cristatum chromosomes. To analyze the structure and cross-species homoeology of A. cristatum chromosomes with wheat, probes for 45 mapped wheat cDNAs covering all seven chromosome groups were localized by FISH. Thirty-four cDNAs hybridized to homoeologous chromosomes of A. cristatum, nine hybridized to homoeologous and non-homoeologous chromosomes, and two hybridized to unique positions on non-homoeologous chromosomes. FISH using single-gene probes revealed that the wheat-A. cristatum collinearity was distorted, and important structural rearrangements were observed for chromosomes 2P, 4P, 5P, 6P and 7P. Chromosomal inversions were found for pericentric region of 4P and whole chromosome arm 6PL. Furthermore, reciprocal translocations between 2PS and 4PL were detected. These results provide new insights into the genome evolution within Triticeae and will facilitate the use of crested wheatgrass in alien gene introgression into wheat.
Keywords: Triticum; Diploidy; Translocation, Genetic; Agropyron; DNA sondy; In Situ Hybridization, Fluorescence; DNA Probes; pšenice; karyotyp; translokace genetická; diploidie; Karyotype; Tandem Repeat Sequences; tandemové repetitivní sekvence; hybridizace in situ fluorescenční; chromozomy rostlin; Chromosomes, Plant